How Much Transparency is Too Much? A Moment-to-Moment Analysis of Viewer Comfort in Response to Animal Slaughter Videos - Troy G. Tarpley; Laura Morgan Fischer; Garrett M Steede; R. Glenn Cummins; Amber McCord (Journal of Applied Communications, 2020)
The Glass Walls project is a series of videos created by the American Meat Institute that works to create increased transparency regarding agricultural industry practices surrounding animal slaughter and carcass fabrication. To assess the impact of the increased transparency presented in these videos, this study examined consumer response to sampled portions of these videos using a novel measurement approach to agricultural communications, continuous response measurement or “dial testing.” Two samples of college students who differed in their level of agricultural involvement provided continuous ratings of perceived comfort while viewing the two videos. Findings indicated that participants with higher agricultural involvement reported less discomfort with the material being presented. Further, critical moments within the videos that elicited a strong uncomfortable response were identified through this novel measurement approach. These moments elicited strong responses, regardless of viewers’ level of agricultural involvement. Results suggested that attempts at increased transparency may elicit discomfort from the consumer. Therefore, practitioners and researchers should seek to develop ways to present the same material, but in a way that creates less discomfort for the audience. In addition to the findings of this study, details regarding the use and need of continuous response measurement in agricultural communications are included.
Keywords: Continuous Response Measurement; Elaboration Likelihood Model; Animal Slaughter; Transparency; Animal Agriculture